2022
DOI: 10.1111/pce.14259
|View full text |Cite
|
Sign up to set email alerts
|

Root hydraulic phenotypes impacting water uptake in drying soils

Abstract: Soil drying is a limiting factor for crop production worldwide. Yet, it is not clear how soil drying impacts water uptake across different soils, species, and root phenotypes.Here we ask (1) what root phenotypes improve the water use from drying soils? and(2) what root hydraulic properties impact water flow across the soil-plant continuum? The main objective is to propose a hydraulic framework to investigate the interplay between soil and root hydraulic properties on water uptake. We collected highly resolved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
41
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 86 publications
(48 citation statements)
references
References 92 publications
7
41
0
Order By: Relevance
“…Another reason could be the soil-root conductance which was not included in the model. This is supported by results reported by Cai et al (2022) who compiled data from several lab experiments and found that, especially in sandy soils, a low soil-root conductance generates a drop in soil water potentials from the bulk soil to the soil root interface and leads to a strong drecrease in leaf water potentials (Abdalla et al 2021). The drop in soil water potential depends on the unsaturated hydraulic conductivity of the rhizosphere, which decreases strongly when the soil dries out.…”
Section: Discussionsupporting
confidence: 75%
“…Another reason could be the soil-root conductance which was not included in the model. This is supported by results reported by Cai et al (2022) who compiled data from several lab experiments and found that, especially in sandy soils, a low soil-root conductance generates a drop in soil water potentials from the bulk soil to the soil root interface and leads to a strong drecrease in leaf water potentials (Abdalla et al 2021). The drop in soil water potential depends on the unsaturated hydraulic conductivity of the rhizosphere, which decreases strongly when the soil dries out.…”
Section: Discussionsupporting
confidence: 75%
“…In this issue, Liao et al (2022) document how deeper root growth by rice under drought stress may be a response to fluctuating soil moisture conditions and identified nodal root diameter class as a key trait linking early season root growth with later season root growth and grain yield based on path analysis and GWAS co‐locations. Cai et al (2022) identified the soil/root gap as a key constraint to water uptake, in contrast to most previous work which focuses on traits to access more water (i.e., drought avoidance). The author proposes a hydraulic framework to explain the interplay between soil and root hydraulic properties on water uptake, introducing the concept of critical soil water potential (ψ c soil ) which corresponds to the point at which plants downregulate transpiration.…”
Section: Water Uptake: More Than Just Deep Root Growthmentioning
confidence: 99%
“…For example, architecture‐scale traits such as root angle can have a major impact on foraging efficiency for immobile and mobile soil nutrients such as phosphate and nitrate, respectively (Schneider et al, 2022). Increasing evidence supports the importance of anatomical‐scale traits, such as root hair length and xylem size, conferring abiotic stress tolerance in crops (Cai et al, 2022; Cornelis & Hazak 2022; Kohli et al, 2022), whilst major steps are being made to dissect molecular‐scale adaptive mechanisms, such as ways roots detoxify metals and metalloids (Kirk et al, 2022; Podar & Maathuis, 2022). Knowledge of these root phenotypes and their underlying regulatory genes is vital for developing future crop varieties better adapted to the challenges presented by global climate change and the pressing need to support more sustainable agricultural practices.…”
Section: Root Phenotypes For the Future: A Range Of Phenotypic Scalesmentioning
confidence: 99%
“…In the soil-plant-atmosphere continuum, the water diffusion resistance through leaves contributes ~30% of the whole plant hydraulic resistance [ 38 ]. In contrast, recent studies have suggested that root hydraulic resistance, including the resistance through radial pathway from root surface to the xylem and that through the root-soil interface, is the major resistance for water diffusion [ 39 , 40 ]. The relative resistance through leaves and roots in rice plants is not known, but we speculate that root hydraulic conductance may vary with growth stages and N supplies, which in turn determines the variation in g s .…”
Section: Discussionmentioning
confidence: 99%